Structural barriers to transformational leadership and the influence of internal organisational context - Blyth, David Ian (Curtin University, 2010)
This thesis explores the potential structural barriers to transformational leadership and the influence of organisational context. Qualitative research was undertaken across two case study firms using grounded research (Glaser & Strauss, 1967; Whiteley, 2004).A number of themes emerged which collectively describe a range of structural barriers to transformational leadership. The empirical evidence of this research highlights the structural barriers and the influence of organisational context on transformational leadership. The themes that emerged and are discussed in this thesis include: understanding and influence of the strategic context; clarity of direction; organisational design; control systems; role context; the change dynamic within the organisation; the degree of empowerment; the organisational culture; the relational context; and the lack of time.From these emergent themes and incorporating the extant literature a number of second order insights also emerged. In particular, the thesis examines the interplay between the levels of work and the nature of transformational leadership; the notion of ‘nested leadership’ where the leader’s leader plays a much stronger role than simple role modelling; and the emergence of a new holism, wherein the dynamic interplay between transactional and transformational leadership is exploredThe research confirms what Fiedler and others have suggested: “we can design situations that allow leaders to utilize their intellectual abilities, expertise and experience more effectively” (Fiedler, 1996, p. 249).